Enhancing sentiment and intent analysis in public health via fine-tuned Large Language Models on tobacco and e-cigarette-related tweets - Elmitwalli, Sherif; Mehegan, John; Gallagher, Allen; Alebshehy, Raouf (Frontiers in Big Data, 2024)
BackgroundAccurate sentiment analysis and intent categorization of tobacco and e-cigarette-related social media content are critical for public health research, yet they necessitate specialized natural language processing approaches.ObjectiveTo compare pre-trained and fine-tuned Flan-T5 models for intent classification and sentiment analysis of tobacco and e-cigarette tweets, demonstrating the effectiveness of pre-training a lightweight large language model for domain specific tasks.MethodsThree Flan-T5 classification models were developed: (1) tobacco intent, (2) e-cigarette intent, and (3) sentiment analysis. Domain-specific datasets with tobacco and e-cigarette tweets were created using GPT-4 and validated by tobacco control specialists using a rigorous evaluation process. A standardized rubric and consensus mechanism involving domain specialists ensured high-quality datasets. The Flan-T5 Large Language Models were fine-tuned using Low-Rank Adaptation and evaluated against pre-trained baselines on the datasets using accuracy performance metrics. To further assess model generalizability and robustness, the fine-tuned models were evaluated on real-world tweets collected around the COP9 event.ResultsIn every task, fine-tuned models performed much better than pre-trained models. Compared to the pre-trained model's accuracy of 0.33, the fine-tuned model achieved an overall accuracy of 0.91 for tobacco intent classification. The fine-tuned model achieved an accuracy of 0.93 for e-cigarette intent, which is higher than the accuracy of 0.36 for the pre-trained model. The fine-tuned model significantly outperformed the pre-trained model's accuracy of 0.65 in sentiment analysis, achieving an accuracy of 0.94 for sentiments.ConclusionThe effectiveness of lightweight Flan-T5 models in analyzing tweets associated with tobacco and e-cigarette is significantly improved by domain-specific fine-tuning, providing highly accurate instruments for tracking public conversation on tobacco and e-cigarette. The involvement of domain specialists in dataset validation ensured that the generated content accurately represented real-world discussions, thereby enhancing the quality and reliability of the results. Research on tobacco control and the formulation of public policy could be informed by these findings.